International economics - Marrewijk, Charles Van (Oxford University Press, 2007)
International Economics contains thiry-two chapters split into two parts with Part One covering International Trade, and Part Two covering International Money. The text covers a broad range of recent developments, with European and global empirical examples and case studies linking theories to the real world